A Study on Childhood Death at a Tertiary Care Level in Ernakulam District - Celine TM (Annals of Medical and Health Sciences Research, 2013)
Background: Childhood mortality is increasing day by day. It will affect the development of the nation. Preventive measures on childhood mortality could be an effective approach for saving child’s life. Aim: To find out the causes of deaths among children below 12 years of age those who were admitted in a teaching hospital during the period from April 2005 to March 2010. Materials and Methods: A retrospective study was conducted with hospitalized patients below 12 years those who died in a Teaching Hospital from April 1, 2005 to March 31, 2010. The data were collected from the registers maintained in the Medical Records Department. The data were analysed by using Microsoft Excel. Z test was applied for the comparison of proportions. P value less than or equal to 0.05 indicates that there is significance difference between the proportions of two groups. Results: Child deaths below 12 years of age during the period April 1, 2005 to March 31, 2010 were 459. Of these deaths 62.0% (285/459) of all child deaths were males and 37.9% (174/459) of all child deaths were females. Most of the deaths were in the neonatal period (deaths within 28 days of life). Most of the deaths occurred due to certain conditions originating in the perinatal period 52.2% (240/459) of all child deaths. Of the deaths occurred due to certain conditions originating in the perinatal period, 60% (144/240) of deaths were due to respiratory and cardiovascular disorders. Conclusion: Neonatal deaths were increasing each year. Conduct Health awareness programmes for reducing the neonatal deaths. And also improve the antenatal and newborn care for reducing the neonatal deaths